Atypical Choroid Plexus Papilloma of the Foramen Luschka in an Adult: A Case Report and Literature Review - Ergun, Ahmet Cemil; Hergunsel, Omer Batu; Calik, lknur; Yildirim, Gokhan; Kaplan, Metin (Georg Thieme Verlag Kg, 2025)
Choroid plexus papillomas are rare tumors of the central nervous system. They are mostly observed during childhood and are commonly located in the lateral ventricles. In adults, they are very rare and usually located in the fourth ventricle. We herein present a case of atypical choroid plexus papilloma of the foramen of Luschka in an adult. A 26-year-old male patient was presented with headache, dizziness, visual loss, and gait disturbance. Cranial imaging revealed a giant mass located in the foramen of Luschka with non-intense homogeneous contrast enhancement. Gross total removal of the tumor was achieved via the left telovelar approach. Transient swallowing difficulty and worsening of the nystagmus were observed in the early postoperative period. The patient was free of symptoms for 3 months postoperatively. The pathological examination yielded a diagnosis of atypical choroid plexus papilloma. We aimed to discuss the clinical findings and surgical treatment of the case.
Keywords: foramen of Luschka; telovelar approach; telovelar approach; atypical choroid plexus papilloma